Pengaruh Indeks Pembangunan Manusia dan Pengangguran Terhadap Kemiskinan di Provinsi Kepulauan Bangka Belitung - Andi Kurniawan Karta Negara; Devi Valeriani (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Timor, 2021)
This study aims to analyze and find out how the influence of the Human Development Index and Unemployment on Poverty in the Province of the Bangka Belitung Islands. The type of research used in this study is a type of quantitative research. There are three variables used in this study, namely the human development index, unemployment and poverty. The analytical tool used in this study is multiple linear regression with panel data. The results showed that partially the Human Development Index variable had a significant negative effect on Poverty in the Province of the Bangka Belitung Islands. Unemployment has a significant positive effect on the Poverty Level in the Province of the Bangka Belitung Islands. While the results of the simultaneous test show that overall the Human Development Index and Unemployment variables have a significant positive effect on poverty in the Province of the Bangka Belitung Islands.